Educação infantil e educação das relações étnico-raciais: motivações docentes, possibilidades e desafios nos centros de educação infantil de Sorocaba (SP) - Garcia, Vanessa Ferreira (Universidade Federal de São Carlos, 2019)
The present research has the objective of analyzing how the education of ethnic-racial relations are understood by the teachers of early childhood education in municipal schools in Sorocaba (SP). The research had a qualitative methodology and theoretical basis in the Studies of Childhood in Brazil; articulated with research on the education of ethnic-racial relations. The methodological stages occurred through questionnaires and semi-structured interviews on the education of ethnic-racial relations, focusing the motivational bases, possibilities and challenges in the implementation of practices of valorization to racial equality. Participants were teachers who work with children from zero to five years of age. Together with the bibliographical and documentary research of the goals set out in the Municipal Education Plan (2015 to 2025) and the Municipal Plan for Early Childhood (2016 to 2026), was made a cut of the current panorama of the city, in order to outline indicators on how education of ethnic-racial relations in children's education is articulated, the difficulties faced and the actions carried out by the teachers. The analysis of the data of the teachers indicates that deepening for actions, formations and collective proposals are considered as difficulties. In this context, actions for the promotion of racial equality occurred, for the most part, on the initiative of teachers who seek external materials and training with their own resources.
Early childhood school and Ethnic-Racial Relations Education: Teacher Motivations, Possibilities and Challenges in Children’s Education Centers of Sorocaba (SP)
Keywords: Educação Infantil. Educação das Relações étnico-raciais. Formação docente.; CIENCIAS HUMANAS::EDUCACAO